2023
DOI: 10.1128/spectrum.03409-22
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between CRISPR-Cas Content and Growth Rate in Bacteria

Abstract: Accumulating evidence indicates that slowing the growth of cultured bacteria could stimulate their CRISPR spacer acquisition. We observed a positive correlation between CRISPR-Cas content and cell cycle duration across the bacteria domain. This observation extends the physiological conclusion to an evolutionary one. In addition, the correlation provides evidence supporting the existence of a trade-off between bacterial growth/reproduction and antiviral resistance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the PGLS correlation analysis of an empirical dataset (Liu et al, 2023), we found that switching dependent and independent variables could lead to a significant incidence of conflicting results. To investigate this further, we simulated the evolution of two traits (ܺ ଵ and ܺ ଶ ) along a binary tree with 100 terminal nodes, using different models and variances for 16000 iterations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the PGLS correlation analysis of an empirical dataset (Liu et al, 2023), we found that switching dependent and independent variables could lead to a significant incidence of conflicting results. To investigate this further, we simulated the evolution of two traits (ܺ ଵ and ܺ ଶ ) along a binary tree with 100 terminal nodes, using different models and variances for 16000 iterations.…”
Section: Discussionmentioning
confidence: 99%
“…A dataset including the empirical minimal doubling times, CRISPR spacer numbers, optimal growth temperature, and prophage numbers of 262 bacteria was extracted from the Supplemental Material Table S1 of Liu et al (2023). The phylogenetic tree of these 262 bacteria was retrieved from the Genome Taxonomy Database (GTDB; accessed April 8, 2022) (Parks et al, 2022).…”
Section: Empirical Datasetsmentioning
confidence: 99%
See 2 more Smart Citations